Исследование объемных акустических волн СВЧ-диапазона, возбужденных встречо-штыревым преобразователем - Решотка, А.Г.; Гайдучок, В.Г.; Вакив, Н.М. (Технология и конструирование в электронной аппаратуре, 2015)
Исследована структура и направление распространения объемных акустических волн, возбужденных встречно-штыревым преобразователем (ВШП) в кристалле ниобата лития, с помощью их визуализации. Показано, что для расчета периода ВШП при конструировании акустооптических дефлекторов СВЧ-диапазона недостаточно использовать лишь подстройку под угол Брэгга. Для определения области распространения таких пучков волн нужно также учитывать параметр Френеля. Досліджено структуру і напрямки розповсюдження об’ємних акустичних хвиль, збуджених зустрічно-штирьовим перетворювачем (ЗШП) в кристалі ніобата літію, за допомогою їх візуалізації. Показано, що для розрахунку періоду ЗШП при конструюванні акустооптичних дефлекторів НВЧ-діапазону недостатньо використовувати лише підстройку під кут Брегга. Для визначення області розповсюдження таких акустичних хвиль потрібно також враховувати параметр Френеля. Excitation of bulk and surface acoustic waves with the interdigital transducer (IDT), which is deposited on the surface of piezoelectric crystal, is widely used in the development of devices in acoustoelectronics and in the design of the microwave acousto-optic deflectors. Excitation of bulk acoustic waves by IDT in the devices on surface acoustic waves leads to the appearance of spurious signals. At the same time excitation of bulk acoustic waves with IDT from the surface of lithium niobate crystals allows creating high frequency acousto-optic deflectors, which makes possible to significantly simplify the technology of their production. Therefore, significant attention is paid to the task of excitation and distribution of bulk acoustic waves with IDT including recent times by the method of simulation of their excitation and distribution. The obtained theoretical results require experimental verification.